Optimized recombinant Bacillus Subtilis 168 whole-cell catalyzes one-step biosynthesis of high fructose syrup - Habimana, Ildephonse; Zhina, Qiao; Muhammad, Aqeel Sahibzada; Harindintwali, Jean Damascene; Al-Adeeb, Abdulqader; Osire, Tolbert; AL-Ansi, Waleed; Hu, Mengkai; Xu, Meijuan; Zhang, Xian; Rao, Zhiming (International Journal of Environment, Agriculture and Biotechnology, 2021)
High fructose syrup is a sweetener that can replace sucrose, which is widely used in the food and beverage industries. In this study, codon-optimized Actinoplanes missouriensis CICIM B0118 (A) derived glucose isomerase heterologous expression was realized in the food-grade strain Bacillus Subtilis 168, and the recombinant Bacillus Subtilis 168/pMA5-xylA was successfully constructed. The whole-cell bioconversion system of D-glucose isomerization to the biosynthesis of D-fructose was optimized. The results showed that the concentration of biocatalysts was DWC 40 g/L, and the concentration of substrate D-glucose was 180 g/L, Mg2+ concentration 10 mmol/L, Co2+ concentration 1 mmol/L, continuous conversion at 70℃、220 R/min for 18 h, D-fructose concentration reached 103.32 g/L, the conversion rate was 57.4%, realizing the high fructose syrup one-step safe biosynthesis. This research provided an experimental and theoretical basis for the industrialized and safe biosynthesis of high fructose syrup and had an important reference value.